Defense against Feeding by Spring Aphid Parasitism in the Upper Leaf Parts of Host Plants - Yuuka Murakami; Hisashi Kawai; Akane Shindo; Eisuke Hasegawa (Psyche: A Journal of Entomology)
In a symbiosis, each participant gains more fitness benefits than is paid in maintenance costs for the symbiosis. The mugwort aphid, Macrosiphoniella yomogicola, is ant-associated, and the host mugwort Artemisia montana is a genet-producing plant that has clonal aboveground shoots. M. yomogicola infests most A. montana shoots from spring to midsummer, and attending ants also repel leaf-eaters of the host plant. However, most aphid colonies become extinct after budding of A. montana inflorescence after early August. A few surviving aphid colonies (1∼3 per genet) produce sexuparae in mid-October. The shoots on which the sexuparae emerged lost most of their fitness because the aphids strongly suppress budding and growth of inflorescence. However, as the shoots are genetic clones of each other, the appearance of stem mothers in the next spring may result in early spreading of the aphids and attending ants to clonal shoots, which would protect the host from leaf-eaters. Here, we show that all shoots on a genet with stem mothers are occupied by aphids and ants much faster than those on a genet without stem mothers. The attending ants repel leaf-eaters to unimportant leaves for the host. Our results suggest that, as the shoots of a genet are all clones, sustaining the aphids on a few shoots may be beneficial to a genet as a whole through kin selection.